2021
DOI: 10.3389/fgene.2021.780780
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pyroptosis-Related Signature for Predicting Prognosis and Indicating Immune Microenvironment Features in Osteosarcoma

Abstract: Osteosarcoma is a common malignant bone tumor with a propensity for drug resistance, recurrence, and metastasis. A growing number of studies have elucidated the dual role of pyroptosis in the development of cancer, which is a gasdermin-regulated novel inflammatory programmed cell death. However, the interaction between pyroptosis and the overall survival (OS) of osteosarcoma patients is poorly understood. This study aimed to construct a prognostic model based on pyroptosis-related genes to provide new insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 76 publications
(74 reference statements)
1
31
0
Order By: Relevance
“…Kaplan-Meier survival analysis in all internal and external cohorts revealed that the overall survival of patients in the high-risk group was consistently worse than that of patients in the low-risk group, indicating the promising accuracy and generalizability of the SLC-based signature in predicting the prognosis of osteosarcoma patients. Time-dependent ROC curves confirmed the specificity and accuracy of our SLC-based signature which was superior to some previously reported prognostic signatures in osteosarcoma ( Fu et al, 2021 ; Zhang et al, 2021 ), since the AUC values of the ROC curves were higher in our research. Furthermore, when patients were divided into different subgroups based on clinical parameters such as gender and age, the prognosis was still poorer in the high-risk group than in the low-risk group in all subgroups, suggesting the signature’s risk stratification utility.…”
Section: Discussionsupporting
confidence: 83%
“…Kaplan-Meier survival analysis in all internal and external cohorts revealed that the overall survival of patients in the high-risk group was consistently worse than that of patients in the low-risk group, indicating the promising accuracy and generalizability of the SLC-based signature in predicting the prognosis of osteosarcoma patients. Time-dependent ROC curves confirmed the specificity and accuracy of our SLC-based signature which was superior to some previously reported prognostic signatures in osteosarcoma ( Fu et al, 2021 ; Zhang et al, 2021 ), since the AUC values of the ROC curves were higher in our research. Furthermore, when patients were divided into different subgroups based on clinical parameters such as gender and age, the prognosis was still poorer in the high-risk group than in the low-risk group in all subgroups, suggesting the signature’s risk stratification utility.…”
Section: Discussionsupporting
confidence: 83%
“…where n represents the number of OS prognosis CRLncs, i is the ith CRLncs, coef is the regression coefficient, and the expression of OS prognosis CRLncs is multiplied by the corresponding regression coefficient and accumulated to obtain the sample risk score (16). The samples in the total sample, training, and test groups were divided into high-and low-risk groups according to the median of the risk score.…”
Section: Construction Of Risk Prognostic Modelmentioning
confidence: 99%
“…Studies have identified pyroptosis-and autophagy-related genes that can predict OS prognosis by using risk prognostic models (16,17). In this study, a novel OS prognosis model was established to explore cuproptosis-related lncRNAs (CRLncs) that can guide OS prognosis and immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…KIRP has a better prognosis in the early stages than clear cell malignancies, but the situation changes drastically after the cancer has spread to distant sites ( Zhao and Eyzaguirre, 2019 ). Pyroptosis has been linked to the emergence and progression of cancers in a growing body of data ( Liu et al, 2021 ; Zhang et al, 2021 ; Zhou et al, 2021 ). Pyroptosis has been found to slow the development of tumors in multiple cancers ( Sharma et al, 2019 ; Chen et al, 2020 ; Fenini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%